Immunohistochemical Analysis of Cytokeratin 7/10/19 and Β-Catenin Protein Expression in Patients with Hepatocellular Carcinoma after Liver Transplantation - Škrtić, Anita; Mrzljak, Anna; Gašparov, Slavko Čolić Cvrlje, Vesna; Naumovski Mihalić Slavica Škegro, Dinko; Filipec Kanižaj Tajana Guštin, Denis; Jadrijević, Stipislav Kocman, Branislav (2011)
Cytokeratin (CK) 10 is associated with invasiveness of hepatocellular carcinoma(HCC). Expression of CK7 and CK19 in HCC suggests worse prognosis based on a hihger HCC recurrence rate in in patients with CK overexpression after liver transplantation (LTx). The most frequently mutated genes in HCC are p53 and beta-Catenin. The aim of this study was to assess the occurrence of CK 7(10/19 and beta Catenin, alone or in combination, in comparison with FISH analysis of 17p13.1, clinico-pathological features and overall survival in HCC transplanted patients.
Projekt MZOS
Projekt MZOS
ENG